Dendroclimatic response of Pinus tabuliformis Carr. along an altitudinal gradient in the warm temperate region of China - Ning, Peng; Zhang, Min; Bai, Tianyu; Zhang, Bin; Yang, Liu; Dang, Shangni; Yang, Xiaohu; Gao, Runmei (Frontiers in Plant Science, 2023)
Introduction Global climate change can affect the sensitivity of tree radial growth to climate factors, but the specific responses of tree radial growth to microclimate along the altitudinal gradient in the long term are still unclear. Methods In this study, the tree-ring width chronologies of Pinus tabuliformis Carr. in Shanxi Province of China were studied at three altitude gradients (1200-1300 m (low altitude), 1300-1400 m (medium altitude) and 1400-1500 m (high altitude)) during 1958-2017. Results The results showed that (1) the climate background could be divided into two periods based on the Mann-Kendall test analysis: 1958–1996 was a stable period (mean annual temperature (MAT)=10.25°C, mean annual precipitation (MAP)=614.39 mm), and 1997–2017 was a rapid change period (MAT=10.91°C, MAP=564.70 mm), indicating a warming and drying trend in the study region. (2) The radial growth of P. tabuliformis at different altitudes showed inconsistent variation patterns. The tree radial growth at low and medium altitudes (CV=27.01% for low altitude and CV=24.69% for medium altitude) showed larger variation amplitudes during the rapid change period than that in the stable period (CV=12.40% for low altitude and CV=18.42% for medium altitude). In contrast to the increasing trend, the tree radial growth rates at the high altitude showed a decreasing trend across years. (3) In the stable period, the radial growth of P. tabuliformis at the low altitude showed a significantly negative response to temperature and a positive response to precipitation in May and June. The tree radial growth at the medium altitude was positively related to precipitation in June and minimum temperature in February. The tree growth at the high altitude was mainly positively correlated with the temperature in May and August. In the rapid change period, the radial growth of P. tabuliformis at the low altitude was affected by more meteorological factors than that in the stable period. Medium-altitude trees were positively influenced by precipitation in June and minimum temperature in January, whereas high-altitude trees responded positively to wind speed in February. (4) Along altitudinal gradients, tree radial growth was more related to temperature than precipitation in the stable period. The tree radial growth at the high altitude during the rapid change period was only affected by wind speed in February, whereas the tree radial growth at low and medium altitudes was mainly affected by temperature to a similar extent during the two periods. Discussion The study indicated that tree growth-climate response models could help deeply understand the impact of climate change on tree growth adaptation and would be beneficial for developing sustainable management policies for forest ecosystems in the transition zone from warm-temperate to subtropical climates.